Age-related changes in the association of resting-state fMRI signal variability and global functional connectivity in non-demented healthy people. (September 2020) - Xie, Wanqing; Peng, Chung-Kang; Shen, Jihong; Lin, Ching-Po; Tsai, Shih-Jen; Wang, Shujuan; Chu, Qianqian; Yang, Albert C.
Highlights: We identified some brain regions have association of age with both rs-fMRI signal variability and gFC respectively. Two typical associations could be observed between SD gFC: positive and negative correlations, though each brain area had its own mode. The influence of signal variability to global functional connectivity was changing with age at the voxel level. Abstract: Research suggests that the aging relates to variability of resting-state fMRI (rs-fMRI) signal and the functional connectivity. However, the association between the spatial and temporal activity of resting-state fMRI signal was less documented. We recruited 477 healthy Han Chinese participants, who were separated into young, middle and old groups to investigate the relationship between the variability and global functional connectivity (gFC) in different age ranges using standard deviation (SD) of time series and gFC, respectively. Our analysis revealed the changing patterns during healthy aging: 1) 17 brain regions(Olfactory_L, Orbital_L etc.) were identified to have significant association of age with both SD and gFC respectively by linear regression analysis; 2) Two typical associations could be observed between SD and gFC: positive and negative correlations; 3) The variation ratio of SD to gFC was changing with age at the voxel level by using unsupervised clustering method. It is the first time to combine voxel-wise variability and gFC together for the study of age-related changes with rs-fMRI signal. This study may provide a new clue for understanding the synchronization of human brain based on SD and gFC due to the effect of aging.